Effect of compound additive on microwave-assisted pyrolysis characteristics and products of Chlorella vulgaris. (October 2021) - Chen, Chunxiang; Qi, Qianhao; Zeng, Tianyang; Fan, Dianzhao; Zhao, Jian; Qiu, Hongfu; Huang, Haozhong
Abstract: In this paper, the microwave-assisted pyrolysis of Chlorella vulgaris was studied by thermogravimetric analyzer (TGA) using absorbent SiC and catalyst TiO2 (compound additive). The effects of compound additive on microwave pyrolysis characteristics, products yield and composition of C. vulgaris were studied under different addition amounts (5%, 10% and 15%) and the mixing ratios (SiC/TiO2 = 10:0, 7:3, 5:5, 3:7, 0:10) of compound additive. The pyrolytic bio-oil were studied by GC-MS analysis. The results showed that the effect of 5% addition amount was better when the mixing ratio was SiC/TiO2 = 5:5 (S5T5). S7T3, S3T7 and S0T10 with 10% addition groups showed a good promoting effect on the pyrolysis of C. vulgaris . The pure TiO2 experimental group with 5% addition had the highest bio-oil yield. With the increase of the TiO2 content in the compound additive at same addition amount, the yield of bio-oil increased. The bio-oil yield of S7T3 and S5T5 experimental groups gradually increased with the increase of addition amount, while that of S3T7 group decreased at first and then increased. SiC, TiO2 and compound additive promote the production of ketones and reduce the acidic substances in bio-oil. Compound additive experimental group had the least amount of acid substances in the pyrolysis bio-oil. Highlights: Transition metal oxide (TiO2 ) was mixed with SiC as compound additive. Effect of the addition amount and mixing ratio of additives on the pyrolysis were analyzed by TGA. The pure TiO2 experimental group with 5% addition had the highest bio-oil yield. GC-MS analysis showed that compound additive could significantly improve the quality of bio-oil.